An Analysis on Contextual Meaning of Selected Songs in Rex Orange County's Album "Pony" and Its Pedagogical Implication - Umi Nur Chotimah; Agus Husein As Sabiq (Journal of English Language Teaching and Linguistics, 2021)
Even though several previous studies discuss meaning analysis in song lyrics, limited studies also conveyed its pedagogical implication in learning. It is essential since songs and music have been widely used in the educational field, especially teaching and learning. Therefore, this research aimed to find out the type of context in the selected songs of Rex Orange County's album entitled Pony, to analyze the contextual meaning found in the songs, and to describe the pedagogical implication of the songs in English learning. The data in this research were in the form of documents, and they were obtained from Rex Orange County's selected songs in Pony album. In analyzing the data, the researchers used content analysis regarding the contextual meaning of Rex Orange County's song lyrics from the album Pony. The results showed that the Pony album contains many contexts and contextual meanings, and there were 40 contexts and 7 context types and contextual meaning in the selected songs of Pony album. These songs can be used as authentic materials to teach "Meaning Through Music" material using the Contextual Teaching and Learning (CTL) approach and Gap Song Filling strategy for the pedagogical implication.